Farmacevtske kognitivne storitve pri zdravljenju z zdravili - pogled farmacevta svetovalca v ambulanti - Premuš Marušič, Alenka (Farmacevtski vestnik, 2013)
Pharmacist cognitive services in different countries in Europe and around the world are carried out in various ways. The range of responsibilities of clinical pharmacists is ranging from prescribing medicine in the United Kingdom and the United States, to pharmacotherapy groups and pharmacist consultant in the Netherlands. Pharmacotherapy Groups and Clinical Pharmacist's Consultation is a currently ongoing development program in Slovenia. Within the program, the clinical pharmacist reviews the treatment of patients. A pharmacotherapy report is made and sent back to the general practitioner for potential therapy change. This development program stimulates further integration of a clinical pharmacist into primary health care and also the optimization of pharmacotherapy for the patient.
Keywords: klinična farmacija; predpisovanje zdravil